Evaluación agronómica para la junta administradora de agua de riego Tiliche San José, cantón Saquisilí, provincia Cotopaxi 2023-2024. - Tipán Mise, Cristian Rafael (2024)
The present research was carried out for the Tiliche – San José Irrigation Water Board, the Saquisilí canton. It was proposed to evaluate the Tiliche San José Irrigation Water Administration Board agronomically. In addition, water samples were taken to determine the degree of arsenic contamination, soil samples were also taken for the same purpose. The agronomic analysis of the board was carried out through a physical - chemical analysis to determine the amount of nutrients available in the soil and compare with the most representative crop. The results obtained in the water analysis to determine the degree of arsenic contamination were that in the three samples taken at the intake, branch 1 and the reservoir exceeded the limit allowed by TULSMA, which is 0.1 mg/l. ; reaching values of 2.77 mg/l, 3.54 mg/l and 1.41 mg/l respectively. For the analysis of the degree of contamination in the soil, it was evident that the samples evaluated from branches 0 – 1 presented a value of 70.6 mg/kg; branch 2 – 3 with a value of 47.8 mg/kg and branch 4 – 5 with 20.9 mg/kg; Branches 6 – 10 presented lower values (2.5 mg/kg) than those established by legislation, which is 12 mg/kg. For the agronomic analysis, the results showed that, for the comparison with corn, nitrogen is found in minimal quantities so a contribution of a nitrogen fertilizer would be needed, while calcium, phosphorus, potassium and magnesium are nutritional elements that are found in high quantities in the soil. It can be concluded that the irrigation water is contaminated by the heavy metal arsenic and therefore the soil is contaminated, affecting the productive area of the sector.